2022
DOI: 10.1111/his.14827
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of cytokeratin 5‐positive pulmonary adenocarcinoma

Abstract: Cytokeratin 5 (CK5) is a marker for pulmonary squamous cell carcinoma; however, CK5 is sometimes present in pulmonary adenocarcinoma (ADC), and there is insufficient information regarding the clinicopathological features of CK5‐positive ADC. We aimed to explore the clinicopathological characteristics of CK5‐positive ADC using immunohistochemistry. We prepared the following two cohorts: a resected cohort containing 220 resected tumours for primarily studying the detailed morphological characteristics, and a tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These findings suggest that ALK–TKI may be less effective in CYFRA21‐1‐positive patients. Previous reports showed a similar trend, in which TKIs were less effective in squamous cell carcinoma, and CK5‐positive lung adenocarcinomas had a worse prognosis 18,20 . It is not clear why TKI efficacy is worse in CYFRA21‐1‐positive ALK lung cancer, but this will need to be examined in future studies, because many ALK‐positive lung cancers are positive for CYFRA21‐1, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…These findings suggest that ALK–TKI may be less effective in CYFRA21‐1‐positive patients. Previous reports showed a similar trend, in which TKIs were less effective in squamous cell carcinoma, and CK5‐positive lung adenocarcinomas had a worse prognosis 18,20 . It is not clear why TKI efficacy is worse in CYFRA21‐1‐positive ALK lung cancer, but this will need to be examined in future studies, because many ALK‐positive lung cancers are positive for CYFRA21‐1, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
“…Previous reports showed a similar trend, in which TKIs were less effective in squamous cell carcinoma, and CK5-positive lung adenocarcinomas had a worse prognosis. 18,20 It is not clear why TKI efficacy is worse in CYFRA21-1-positive ALK lung cancer, but this will need to be examined in future studies, because many ALK-positive lung cancers are positive for CYFRA21-1, as shown in our study. Furthermore, our study found that patients with high tumor markers were more likely to have poor PS and visceral metastases.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations